آزاد کشمیر میں شادی بیاہ کی تقریبات میں ہندوانہ رسوم کی آمیزش :ایک تحقیقی مطالعہMixture of Hindu Rituals in Wedding Ceremonies in Azād Kashmīr: A Research Study (Al-Qamar, 2021)
With the beginning and evolution of society, customs and traditions are also born. Rituals do not appear suddenly in any society but there are ancient beliefs and ideologies behind them. Similarly, their customs and traditions have a profound effect on the civilization and culture of the nations. The Muslims of Azad Kashmir are also suffering the loss of life and property due to the frivolous customs of the Hindus. As Muslims, our way of life must reflect the teachings of Islam. For some time now, the Muslims of Azad Kashmir have been involved in some superstitions and rituals in marriage, that is completely contrary to the teachings of Islam. in this context, the article under consideration is of utmost importance and there is an urgent need to work on it. This article will examine the superstitions of Muslim families in Azad Kashmir in their marriages, and their rituals have been described in the light of Islamic teachings.
Keywords: Azād Kashmīr; Hindu Rituals; Wedding Ceremonies; Mixture; study